2020
DOI: 10.1590/1807-1929/agriambi.v24n8p520-527
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of common bean crops fertigated with treated sewage and mineral fertilizer

Abstract: The water deficit in arid and semiarid regions and the high cost of fertilizers are factors for the study of application of sewage on agricultural crops. Therefore, the objective of this study was to evaluate the effect of application of different doses of treated sewage from the tertiary treatment (TS-3), and mineral fertilizer on the yield and production components of common bean plants. The experiment was conducted in Janaúba, MG, Brazil, using a randomized block design, with four repetitions, in a split-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Considering the treatment averages, for drip irrigation installed at 20 cm depth, the potassium concentration was higher, indicating the ability of synthetic sanitary sewage to provide nutrients at desired soil depths (Figure 3). Araújo et al [3] found that the agricultural use of sanitary sewage is an alternative to provide water and nutrients for plants and recycle nutrients for the soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the treatment averages, for drip irrigation installed at 20 cm depth, the potassium concentration was higher, indicating the ability of synthetic sanitary sewage to provide nutrients at desired soil depths (Figure 3). Araújo et al [3] found that the agricultural use of sanitary sewage is an alternative to provide water and nutrients for plants and recycle nutrients for the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The disposal of sanitary sewage in agriculture is a sustainable way to provide water and nutrients to plants while recycling nutrients in the soil [3]. However, this disposal of sanitary sewage into the soil must be carefully managed, as uncontrolled application can lead to soil salinization, clay dispersion [4,5], and contamination of plants, humans, and the environment, especially when applied through methods such as sprinkler irrigation.…”
Section: Introductionmentioning
confidence: 99%